Cerebello-spinal tDCS in ataxia: A randomized, double-blind, sham-controlled, crossover trial. (18th September 2018) - Benussi, Alberto; Dell'Era, Valentina; Cantoni, Valentina; Bonetta, Elisa; Grasso, Roberto; Manenti, Rosa; Cotelli, Maria; Padovani, Alessandro; Borroni, Barbara
Abstract : Objective: To investigate whether a 2-week treatment with cerebellar anodal and spinal cathodal transcranial direct current stimulation (tDCS) could reduce symptoms in patients with neurodegenerative ataxia and could modulate cerebello-motor connectivity at the short and long terms. Methods: We performed a double-blind, randomized, sham-controlled, crossover trial with cerebello-spinal tDCS (5 d/wk for 2 weeks) in 20 patients with neurodegenerative ataxia. Each patient underwent a clinical evaluation before and after real tDCS or sham stimulation. A follow-up evaluation was performed at 1 and 3 months with a crossover washout period of 3 months. Cerebello-motor connectivity was evaluated with transcranial magnetic stimulation at baseline and at each follow-up. Results: Cerebello-spinal tDCS showed a significant improvement in all performance scores (Scale for the Assessment and Rating of Ataxia, International Cooperative Ataxia Rating Scale, 9-Hole Peg Test, 8-m walking time), in motor cortex excitability, and in cerebellar brain inhibition compared to sham stimulation. Conclusions: A 2-week treatment with cerebello-spinal tDCS reduces symptoms in patients with ataxia and restores motor cortex inhibition exerted by cerebellar structures. Cerebello-spinal tDCS might represent a promising future therapeutic and rehabilitative approach in patients with neurodegenerative ataxia, still an orphan disorder of any pharmacologic intervention. Clinical trial registration: NCT03120013. Classification of evidence: This study provides Class II evidence that cerebello-spinal stimulation is effective and safe in cerebellar ataxia.